If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8t + 16 = 3t + -6t + 8t + -34 Reorder the terms: 16 + 8t = 3t + -6t + 8t + -34 Reorder the terms: 16 + 8t = -34 + 3t + -6t + 8t Combine like terms: 3t + -6t = -3t 16 + 8t = -34 + -3t + 8t Combine like terms: -3t + 8t = 5t 16 + 8t = -34 + 5t Solving 16 + 8t = -34 + 5t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-5t' to each side of the equation. 16 + 8t + -5t = -34 + 5t + -5t Combine like terms: 8t + -5t = 3t 16 + 3t = -34 + 5t + -5t Combine like terms: 5t + -5t = 0 16 + 3t = -34 + 0 16 + 3t = -34 Add '-16' to each side of the equation. 16 + -16 + 3t = -34 + -16 Combine like terms: 16 + -16 = 0 0 + 3t = -34 + -16 3t = -34 + -16 Combine like terms: -34 + -16 = -50 3t = -50 Divide each side by '3'. t = -16.66666667 Simplifying t = -16.66666667
| 1/7(x+7)=1/14(2x+14) | | a/6=20 | | 2/3y-1/6y+4=18 | | 3-4n=-12-7n | | 5n/10=25 | | 13=3w-5 | | 6b+3=7+2b | | 5/6k=7/18 | | x/14-5x+2/49=3x-4/7 | | 8(8-7a)=176 | | 1/n=3/9 | | 10(x+1)=10 | | 9=13-x+5x | | 28/35=40/j | | 4(-1)=-12-(-9) | | t/6=96/16 | | 5m^2+17m-66=0 | | 3(1)=1-2(2) | | 3(2x)-2=2(3x+9) | | 3u-9=18 | | 3(not-2)-19=5+2(n+5) | | 2(1)=0-2 | | 15/3.9 | | -6.6z-2.8+6.7z=28 | | 45/x=15/3 | | m+17=2m | | 59+3y-27=13y-10-4y | | 2a-1=a+4 | | 6(x+4)=2(3x+5)+14 | | 0.5x+14.2=x-1.45 | | 2/3n=10 | | 0.6x+14.2=x-1.45 |